Approaches to the usage of machine translation systems for the organization of independent work of students of a pedagogical university with English-language scientific texts - Tatiana N. Suvorova; Lyubov A. Shunina; Ivan V. Shunin (RUDN Journal of Informatization in Education)
Problem statement. The article describes and substantiates ways to solve the problem of the lack of approaches to the usage of machine translation systems in the organization of independent work of students of a pedagogical university with Englishlanguage scientific texts. The purpose of the described research was to practically confirm the effectiveness of the developed approaches to the study of machine translation systems of scientific texts by students in order to increase the effectiveness of their independent and research work. Methodology . The method of analyzing scientific and methodological sources and normative documents related to the problem of organizing independent work of students of a pedagogical university with English-language scientific texts is applied. Methods of comparison and generalization of the obtained results are used in order to determine the effectiveness of the proposed online course “Machine translation of scientific texts”. A longitudinal experimental study was conducted. 28 students enrolled in the basic bachelor’s and master’s degree programs of the Moscow City University were involved in the experimental training. As a part of the ascertaining stage, empirical information was collected and analyzed, which made it possible to clarify the hypothesis of the study and confirm its relevance. At the formative stage of the experiment, the implementation of the developed online course was carried out. At the generalizing stage, the results of the experiment were summarized. Results . As a result of teaching students of the pedagogical university the basics of using machine translation systems of English-language texts in their independent work, the following results were achieved: students formed an idea about the features of translating scientific texts from a foreign language into Russian; studied the possibilities of modern machine translation services; compiled a terminological glossary; acquired skills in machine translation of scientific texts using specialized CAT programs. As a result, the overwhelming majority of students confidently turn to scientific sources in a foreign language by understanding the principles of machine translation; they actively study foreign professional experience, as well as its application in independent research activities. Conclusion . The effectiveness of the developed model of approaches to the use of machine translation systems as means of informatization of scientific, educational and practical activities in the organization of independent work of students of a pedagogical university with English-language scientific texts has been experimentally proved.